Memory Activism between Values and Interests: Monuments, Museums and Institutions - Davoliūtė, Violeta; Cauvin, Thomas; Budrytė, Dovilė (Politologija, 2024)
Special Issue of PolitologijaGuest-edited byVioleta DavoliūtėVilnius UniversityThomas CauvinUniversity of LuxembourgDovilė BudrytėGeorgia Gwinnett College
Keywords: -